ANALISIS PENGARUH POLITICAL CONNECTION DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN - Tri Wulandari; Raharja Raharja (Diponegoro Journal of Accounting, 2013)
The performance of company can not be separated from the influence of the environment in which the company was founded. One of the environmental factors that affect the company’s performance is politics. A country’s political related to public policy, including policies for business. Therefore, between politics and business are interrelated, so there is a term politically connected firms. Besides politics, the performance of company is also affected by the ownership structure. This research aims to analyze the effect of political connection and ownership structure on firm performance. Ownership structure consists of institutional ownership and public ownership. This research uses two control variable, firm size and leverage.The dependent variable in this research is the performance of the company as measured by Return on Asset ratio. The independent variables were tested, namely political connection, institutional ownership, and public ownership. This research uses secondary data, namely the annual finacial statements of listed companies in Indonesia Stock Exchange for the years 2009, 2010, and 2011. The number of sample firms is 57 firms. Data analysis model used was multiple regression analysis with the help of SPSS software.The results shows that the firm performance of the political connection firms is lower than the firms non political connection. It is seen from the probability value of 0,047 with the regression coefficients are negative direction. Ownership structure of both institutional ownership and public ownership doesn’t affect the firms perfomance. Probability value of institutional ownership at 0,279 and probability value of public ownership at 0,112.